Ad Solaria, identificazione di una stazione di sosta : nuove prospettive dallo scavo di un complesso romano a Calenzano (Firenze) - Pasini, Daria (BAR international series, 2021)
This study identifies the road station ad Solaria, which recurs in several ancient sources, starting with the Tabula Peutingeriana. It interprets the data coming from this site, which was an emergency excavation managed by the author, allowing a reconsideration of several aspects of the archaeological recognizability of Roman road stations. The volume also includes extended chapter abstracts in English.